Ultrastructural Re-Arrangements in Hypothalamus of Aged Rats After Rhythmic Extreme Cold Exposures - Kulik, Vladimir V.; Babijchuk, Vladislav G. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):185.